The Biopsychosocial Burden of Prostate Biopsy at the Time of Its Indication, Procedure, and Pathological Report - Walker W. Laranja; Brunno C. F. Sanches; Brunno R. I. Voris; João C. C. Alonso; Fabiano A. Simões; Ronald F. Rejowski; Leonardo O. Reis (Prostate Cancer)
Purpose. To explore the burden of prostate biopsy at the time of its indication, procedure, and pathological report in the prostate cancer-screening scenario that is neglected and underestimated in the literature. Methods. Prostate biopsy was offered to 47 consecutive patients with prostate-specific antigen (PSA) over 4 ng/dl or suspicious digital rectal examination (DRE) of whom 16 had undergone a biopsy. Comprehensive validated questionnaires at Time 0 (prebiopsy), Time 1 (before diagnosis, 20 days after biopsy), and Time 2 (after diagnosis, 40 days after biopsy) accessed patients' erectile (IIEF-5) and voiding (IPSS) functions, Beck scales measured anxiety (BAI), hopelessness (BHS), and depression (BDI), added to the emotional thermometers including five visual analog scales for distress, anxiety, depression, anger, and need for help. The Mann-Whitney or Friedman tests were obtained among times and studied variables. Results. Prostate biopsy did not significantly impact patients' erectile and voiding functions while a higher Beck anxiety index (BAI) was observed at Time 0 (6.89 ± 6.33) compared to Time 1 (4.83 ± 2.87), p=0.0214, and to Time 2 (4.22 ± 4.98), p=0.0178. At Time 0, patients that experienced a previous biopsy presented higher distress (3.1 ± 3.0 vs. 1.6 ± 2.3), p=0.043, and emotional suffering thermometer scores (2.3 ± 3.3 vs. 0.9 ± 2.4) compared to those undergoing the first biopsy, p=0.036. At Time 2, patients with positive biopsies compared with those with negative ones showed no significant difference in outcome scores. The sample power was >90%. Conclusions. To be considered in patients' counseling and care, the current study supports the hypothesis that the peak burden of prostate biopsy occurs at the time of its indication and might be higher for those experiencing rebiopsy, significantly impacting patients' psychosocial domains. Trial Approval. This trial is registered under number NCT03783741.